Controle estatístico de qualidade de irrigação e fertirrigação por gotejamento na cultura da uva - Klein, Márcio Roberto (2013)
Irrigated agriculture has great potential for productivity. The proof is that the area for irrigated agriculture in the world, representing approximately 20 % of the total area destined to agriculture, is responsible for approximately 45 % of the total harvested. In order to maximize the profits of agricultural products, it is necessary to comply with various protocols of good practice, which include, in addition to maintaining a quality standard specific to the products, reducing environmental impact and generating benefits to communities involved in the agricultural production. Then, it is possible to achieve a more profitable niche market. To achieve the agricultural products standards required by the market, there must be a level of control in the processes of cultural practices in the water and fertilizer application. Statistical quality control processes were implemented in the industries of Japan after the Second World War and it is considered the tool responsible for the triumph of manufacturing, service and quality processes for the country. Quality control is perfectly adaptable for the agricultural production system. Therefore, this research aimed to assess the distribution of water and fertilizer in a drip irrigation system and determine the limits of statistical process and process capabilities in irrigation and fertigation under different pressures and concentrations of NPK (Nitrogen, Phosphorus and Potassium). The experiment was conducted in the municipality of Salto do Lontra, in a farm that participates in the Family Irrigation Project developed by Unioeste University. There were four inlet pressures: 150, 200, 250, and 300 kPa, combined with three NPK solution concentrations: 0, 200, and 400 mgL-1. In the evaluations, two methods were used for sampling, one with 16 points and another with 32 points. Using the average flow rate, CUC and CUD were calculated both methodologies. The classification of CUC was "excellent" for all assessments. Using CUD, 83.4 % of ratings were "excellent" with the sampling methodology with 16 points, and 97.3 % with the methodology of 32 points. None of the processes were considered acceptable for process use, when statistical control limits were calculated. The processes of irrigation and fertigation more suitable for improvement and consequent process capability increase were those with inlet pressures of 150 and 200 kPa.